"THE ISSUE OF KIDS' PSYCHOLOGICAL PREPARATION FOR FORMAL EDUCATION": Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In the modern world, there is a trend of increasing demand preparing children for school from preschool age. There are many different ones opinions of scientists on determining school readiness indicators, taking into account the understanding of school readiness from in terms of psychological and pedagogical features. In this article, an an attempt is made to summarize existing theories of school understanding preparation, as well as an experimental study of the preparation of children Kindergarten training is provided.